Digital Native Children In Elementary Education: Transformation Of Learning Behavior In Generation Alpha - Risza Presty Rumani (PT. Anagata Sembagi Education, 2026)
The emergence of Generation Alpha as digital native children poses transformative challenges and opportunities for elementary education worldwide. These learners, born after 2010, have grown up immersed in digital environments, reshaping their cognitive processes, social interactions, and learning behaviors. This systematic literature review synthesizes findings from 23 peer-reviewed studies published between 2021 and 2024 to examine the transformation of learning behaviors among digital native children in primary school settings. The review explores the integration of digital technologies—including artificial intelligence tools, gamification, mobile devices, digital storytelling, and immersive environments—and their effects on academic engagement, digital literacy, collaborative skills, critical thinking, and motivational outcomes. Findings indicate that well-structured digital technology integration significantly enhances learning engagement (78%), digital literacy skills (85%), and student motivation (88%). However, the literature also reveals persistent challenges including the digital divide, teacher preparedness, and concerns regarding excessive screen time and digital dependency. This review contributes a synthesized framework for understanding how schools can responsibly support Generation Alpha's learning potential while addressing socio-cultural and equity concerns in the digital age